Three‐Dimensional Printed Cardiac Models for Focused Cardiac Ultrasound Instruction. (24th September 2018) - Ochoa, Sebastian; Segal, Jonathan; Garcia, Noah; Fischer, Ernest A.
Abstract : Background: Focused cardiac ultrasonography (FCU) is an increasingly integral component of routine medical training and practice. While various instructional methods have been described, few attempts have been made to incorporate a physical 3‐dimensional (3D) instructional aid. Objective: The aim of this study was to determine if a 3D printed heart model workshop for FCU instruction leads to equivalent structure recognition and scanning ability compared to traditional didactic FCU instruction. Intervention: Twenty first‐year medical students with no point‐of‐care ultrasonography experience were randomly assigned to a traditional lecture (n = 10) or a 3D printed heart model workshop (n = 10). Written examinations at 0 and 3 months as well as image acquisition at 3 months were compared. Results: The median scores from the initial written structure identification in the traditional and 3D heart groups were 74% and 90%, respectively ( P  = 0.7). The second written exam at 3 months yielded median scores of 56% and 58% in the traditional and 3D heart groups, respectively ( P  = 0.8). The average scores on the image acquisition practical at 3 months were 3.3 of 5 and 2.7 of 5 ( P  = 0.1) in the traditional and 3D heart groups, respectively. Conclusions: Utilizing 3D heart models in an FCU workshop format results in similar skill acquisition and knowledge retention as traditional didactics. The 3D heart models are relatively inexpensive, portable, and reusable, enabling learners to practice repeatedly and at flexible intervals. The reduction in ongoing expenses and the ability to teach large groups may decrease training costs as well as the need for local faculty expertise.